THE USE OF FIGURATIVE LANGUAGE AND THE STRUCTURAL STRATEGY IN TORAJAN ORAL LITERATURES: EFFORTS TO LOCAL LANGUAGE PRESERVATION - Herianah, Herianah; Asis, Abdul (Kementerian Pendidikan dan Kebudayaan, 2021)
This study aimed to describe the use of figurative language and the structural strategies in Torajan oral literatures. The method used in this research was a qualitative research. This research was a literature research, thus it was done through reading-listening and noting. The research result showed that there were several figurative language in Torajan oral literatures, for instance, sarcasm structural strategy, the linking figurative of metonymy, and the comparison figurative of allegory in the story of Babuqsolong; the figurative of allegory, irony, and hyperbole in the story of Londorundum; and the figurative of personification and parallelism in the story of Bunga Alluq sola Dalitau. From the three, the story of Londorundum had the most used of figuratives language and structural strategies. The use of figurative language and structural strategies is one of the effort to the local languages preservation as well as supported the national cultural preservation as nationâ€™s asset.Â